Kinerja Kepadatan Spirulina Sp. yang diberi Salinitas Berbeda pada Meda Kultur Walne : Kepadatan Spirulina pada Salinitas berbeda - Hasim Hasim; Mohammad Akram; Yuniarti Koniyo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
This study aims to determine the population density of Spirulina sp cultured on Walne media with different salinities (20‰, 25‰, 30‰, 35‰) on a laboratory scale. The method used is an experimental method using a completely randomized design. The results showed that different salinity had an effect on the cell density level of Spirulina sp for 10 days. The maximum total biomass density of Spirulina sp was 6071889.597 cells/ml at 30‰ salinity treatment, and the lowest biomass growth was 4187919.321 cells/ml at 20‰ salinity. Statistical analysis (ANOVA) showed that the difference in salinity to the density of Spirulina sp cells had a significant effect where the value (Fcount > Ftable) was at the 5% level.